A Review Into the Effects of Pamidronic Acid and Zoledronic Acid on the Oral Mucosa in Medication-Related Osteonecrosis of the Jaw - Bullock, George; Miller, Cheryl A.; McKechnie, Alasdair; Hearnden, Vanessa (Frontiers in Oral Health, 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is a growing problem without an effective treatment, presenting as necrotic bone sections exposed via lesions in the overlying soft tissue. There is currently a lack of clarity on how the factors involved in MRONJ development and progression contribute to disease prognosis and outcomes. Bisphosphonates (BPs), the most common cause of MRONJ, affect bone remodelling, angiogenesis, infection, inflammation and soft tissue toxicity, all of which contribute to MRONJ development. This article reviews the cellular mechanisms through which BPs contribute to MRONJ pathology, with a focus on the effects on cells of the oral mucosa. BPs have been shown to reduce cell viability, reduce proliferation, and increase apoptosis in oral keratinocytes and fibroblasts. BPs have also been demonstrated to reduce epithelial thickness and prevent epithelial formation in three-dimensional tissue engineered models of the oral mucosa. This combination of factors demonstrates how BPs lead to the reduced wound healing seen in MRONJ and begins to uncover the mechanisms through which these effects occur. The evidence presented here supports identification of targets which can be used to develop novel treatment strategies to promote soft tissue wound healing and restore mucosal coverage of exposed bone in MRONJ.